Lightning Performance of Extra High Voltage 500 kV Lines at East Java- Indonesia - Zoro, Reynaldo; Y. Pramono, Eko (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2008)
Extra High Voltage (EHV) 500 kV transmission lines has higher insulation strength against overvoltages produced by lightning strikes compare to lower transmission lines voltage such as 150 kV or 70 kV transmission lines. Observation was carried out at EHV 500 kV Paiton-Kediri line located at east Java island of Indonesia. This line has operated for more than five-years. In fact is there were many insulators were broken by lightning strikes, especially during rainy season. A large number of broken insulator at many towers deterioted performance of the lines, in which many line outages occured. This study presents the evaluation results of performance of the lines concerning its robustness agains lighting strikes. Investigation of the characteristics of lightning strikes in the area along the lines was carried out. From this observation and study it founds that some towers need to be improved to have better performance against overvoltage due to direct lightning strikes to the towers. By using Severity index methodology, local lightning data and innovation technology for lightning protection system significant results were derived.